Mobile service usage behavior in Korea: an empirical study on consumer acceptance of innovative technologies - Sawng, Yeong-Wha; Kim, Seung-Ho; Lee, Jungmann; Oh, Young Sam (Technological and Economic Development of Economy, 2011)
Whilst mobile services have grown to a sizeable market in recent years, and leaps and bounds have been made in related technology, consumers’ usage behavior with regard to these services has received little attention from researchers. Studies on related topics are few and scarce, if compared, for example, to studies on information systems or web services. The main purpose of this study is to investigate consumers’ usage behavior in mobile services to provide pointers for future development of this field. Specifically, this study attempts to identify variables influencing the use of mobile service consumers. We developed an information technology acceptance model to determine usage characteristics and usage trends in mobile services and predict consumers’ usage behavior based on patterns discerned from these characteristics and trends. Information technology acceptance models are a useful tool for understanding the behavior of consumers of services such as mobile services, combining aspects of a technology and service good, from the perspective of behavioral science. This study, comprehensively concerned with mobile service marketing-related issues, considers both factors influencing consumers’ usage behavior and also technical aspects of services. Factors influencing the behavior of mobile service consumers are investigated empirically, by examining them in a real-world context. The expected outcomes of this study are as follows: First, it will predict consumers’ usage behavior with regard to mobile services based on usage characteristics at the level of task management, and discern identifiable and recurring patterns. Second, it will awaken providers to the importance of technical and functional performance and a clear understanding of consumers’ needs for the success of marketing mobile services.